2015
DOI: 10.1016/j.cub.2015.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Integrin Adhesions Suppress Syncytium Formation in the Drosophila Larval Epidermis

Abstract: Summary Integrins are critical for barrier epithelial architecture. Integrin loss in vertebrate skin leads to blistering and wound healing defects. However, how Integrins and associated proteins maintain the regular morphology of epithelia is not well understood. We found that targeted knockdown of the integrin focal adhesion (FA) complex components βIntegrin, PINCH, and Integrin-linked kinase (ILK), caused formation of multinucleate epidermal cells within the Drosophila larval epidermis. This phenotype was sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 48 publications
4
52
0
Order By: Relevance
“…These observations indicate that patterning and the ability of progenitors to undergo differentiation are likely to be insufficient for appropriate blastema assembly. Integrins can control cell proliferation, survival, migration and adhesion to participate in stem cell/niche interactions, wound healing and formation of tissue barriers among other outputs (Tanentzapf et al, 2007;Goulas et al, 2012;Maartens and Brown, 2015;Wang et al, 2015). Our results suggest that integrins have a prominent role in the organization of regenerative tissue.…”
Section: Discussionmentioning
confidence: 68%
“…These observations indicate that patterning and the ability of progenitors to undergo differentiation are likely to be insufficient for appropriate blastema assembly. Integrins can control cell proliferation, survival, migration and adhesion to participate in stem cell/niche interactions, wound healing and formation of tissue barriers among other outputs (Tanentzapf et al, 2007;Goulas et al, 2012;Maartens and Brown, 2015;Wang et al, 2015). Our results suggest that integrins have a prominent role in the organization of regenerative tissue.…”
Section: Discussionmentioning
confidence: 68%
“…whether JNK induces cell fusion only by inhibiting JAK/STAT signaling, or alternatively, whether JNK directly controls the fusion process in addition to suppressing JAK/ STAT signaling. Because JNK activation, but not loss of JAK/STAT signaling, induced cell fusion in the absence of wounding (Wang et al, 2015; data not shown), the former hypothesis must be rejected. To verify this idea in the context of wound healing, we blocked JAK/STAT signaling by overexpressing dome DN and simultaneously blocked JNK by overexpressing bsk DN .…”
Section: Jnk Suppresses Jak/stat Activation In the Wound Vicinitymentioning
confidence: 97%
“…We tested whether JAK/STAT pathway activation could suppress JNK-induced cell fusion by overexpressing constitutively active hep (hep CA ) and hop together in a patch of dorsal epidermal cells (Wang et al, 2015). In control groups, hop overexpression did not induce cell fusion (Fig.…”
Section: Jnk Suppresses Jak/stat Activation In the Wound Vicinitymentioning
confidence: 99%
See 2 more Smart Citations